2014
DOI: 10.1038/npjpcrm.2014.18
|View full text |Cite
|
Sign up to set email alerts
|

Application of a novel socioeconomic measure using individual housing data in asthma research: an exploratory study

Abstract: Background:A housing-based socioeconomic index (HOUSES) was previously developed to overcome an absence of socioeconomic status (SES) measures in common databases. HOUSES is associated with child health outcomes in Olmsted County, Minnesota, USA, but generalisability to other geographic areas is unclear.Aim:To assess whether HOUSES is associated with asthma outcomes outside Olmsted County, Minnesota, USA.Methods:Using a random sample of children with asthma from Sanford Children’s Hospital, Sioux Falls, SD, US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 36 publications
1
20
0
1
Order By: Relevance
“…28-31 Briefly, geocoded address information was used to match study subject address to geographic reference data and real property data from the Assessor's Office of the county government. A standardized HOUSES Index score was formulated by summing z-scores for 4 real property features (value, square footage, number of bedrooms and number of bathrooms) with a higher HOUSES Index score indicating a higher SES.…”
Section: Methodsmentioning
confidence: 99%
“…28-31 Briefly, geocoded address information was used to match study subject address to geographic reference data and real property data from the Assessor's Office of the county government. A standardized HOUSES Index score was formulated by summing z-scores for 4 real property features (value, square footage, number of bedrooms and number of bathrooms) with a higher HOUSES Index score indicating a higher SES.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, these same health outcomes, defined by physician diagnosis or predetermined criteria, were also significantly associated with our original HOUSES index. [7][8][9][10][11][12][13] The performance of modified HOUSES for objective measure-based health outcomes can be expected to be similar to these findings. HOUSES, which is developed based on real property data for US taxation purposes, may not work well in other countries where housing data are not routinely collected or made publicly available in databases, or even in communities within the USA where housing assessments are infrequent or of poor quality.…”
Section: Discussionmentioning
confidence: 81%
“…While the HOUSES index developed in Olmsted County, MN, and was validated in Jackson County, MO, in the original study, this index was further validated to a different tax jurisdiction and real property data system in Sioux Falls, South Dakota. 12 Correlation of HOUSES with the health-related outcomes of childhood obesity, low birth weight and smoking were evaluated because the association between these outcomes and SES has been well demonstrated. [17][18][19] To assess whether fewer housing-related characteristics could be used, the relative influence (RI) of each characteristic for predicting the health outcomes (obesity, low birth weight and smoking exposure) was estimated using gradient boosting machine (GBM) models under logistic regression model frameworks.…”
Section: Study Participants and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Harris et al [26] utilized a housing based index of SES called HOUSES derived from publicly available housing data from the local government for a group of children with asthma between the ages of 4 to 18 years that were being treated at a single institution. For the 58 subjects with available HOUSES and Asthma Control Test (ACT) data, the authors showed that it correlated with traditional measures of SES except for parental education, and also with asthma morbidity.…”
Section: Discussionmentioning
confidence: 99%